2009
DOI: 10.1108/14777260910942542
|View full text |Cite
|
Sign up to set email alerts
|

The views of physicians and politicians concerning age‐related prioritisation in healthcare

Abstract: 2 ABSTRACT Purpose of this paperThe aim of this study was to describe the view of age-related prioritisation in health care among physicians and healthcare politicians and to compare their views regarding gender and age. MethodologySwedish physicians (n=390) and politicians (n=310), mean age 52 years, answered an electronic questionnaire concerning age-related priority setting in healthcare. The questionnaire had fixed response alternatives with possibility of adding comments. FindingsA majority of the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Other demographic factors such as job, age, gender and marital status do partly associate and play a significant role. These findings are consistent with other studies where these criteria for prioritizing medical services have also controversial results . However, other findings indicate that personal characteristics such as gender, age, education are context specific of choices in health.…”
Section: Discussionsupporting
confidence: 91%
“…Other demographic factors such as job, age, gender and marital status do partly associate and play a significant role. These findings are consistent with other studies where these criteria for prioritizing medical services have also controversial results . However, other findings indicate that personal characteristics such as gender, age, education are context specific of choices in health.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the politicians (61 %) but only 28 % of the physicians thought that regional healthcare politicians should have the greatest influence. When politicians and physicians were asked about their views concerning old age as a criterion for prioritisation, the results indicated that the former referred to ethical principles as a basis for their standpoints while the latter often referred to the importance of biological rather than chronological age [9]. This might indicate that the two categories of decision makers base their decisions on different premises.…”
Section: Introductionmentioning
confidence: 93%
“…In most of the questions the participants were given the chance to comment on the question and/or their response. This paper presents the responses to 11 questions concerning resource allocation (Tables 2-4, Figure 1), the answers to the questions concerning age-related prioritisation have been presented elsewhere [9]. The questionnaire was originally developed based on a review of the literature and on the three ethical principles: the principle of human dignity; the principle of need and solidarity and the cost-efficiency principle.…”
Section: The Questionnairementioning
confidence: 99%
“…The second factor highlights the aged-based rationing. Although it can be framed within a more general principle of favoring the worst-off, we decided to keep it apart, mainly because favoring younger patients is one of the most debated discrimination factors in healthcare accessing (McGough et al, 2005;Werntoft and Edberg, 2009;Reese et al, 2010;Callahan, 2012;Morreim et al, 2014). Finally, achieving efficiency was depicted by the preferences toward the cheapest and effective treatments, as well as those that ensure future savings for the health system.…”
Section: Main Rationing Principles That Support Patients' Prioritizationmentioning
confidence: 99%